Musa genetics - Ortíz, R. (1995)
The triploid nature of plantain and its pattern of inheritance should have represented a challenge and an incentive for geneticists. However, few genetic and cytological investigations have been done in Musa spp. Both banana and plantain have been ignored and neglected as material for basic genetic research.